Mediators of Yoga and Stretching for Chronic Low Back Pain. (17th April 2013) - Sherman, Karen J.; Wellman, Robert D.; Cook, Andrea J.; Cherkin, Daniel C.; Ceballos, Rachel M.
Abstract : Although yoga is an effective treatment for chronic low back pain, little is known about the mechanisms responsible for its benefits. In a trial comparing yoga to intensive stretching and self-care, we explored whether physical (hours of back exercise/week), cognitive (fear avoidance, body awareness, and self-efficacy), affective (psychological distress, perceived stress, positive states of mind, and sleep), and physiological factors (cortisol, DHEA) mediated the effects of yoga or stretching on back-related dysfunction (Roland-Morris Disability Scale (RDQ)). For yoga, 36% of the effect on 12-week RDQ was mediated by increased self-efficacy, 18% by sleep disturbance, 9% by hours of back exercise, and 61% by the best combination of all possible mediators (6 mediators). For stretching, 23% of the effect was mediated by increased self-efficacy, 14% by days of back exercise, and 50% by the best combination of all possible mediators (7 mediators). In open-ended questions, ≥20% of participants noted the following treatment benefits: learning new exercises (both groups), relaxation, increased awareness, and the benefits of breathing (yoga), benefits of regular practice (stretching). Although both self-efficacy and hours of back exercise were the strongest mediators for each intervention, compared to self-care, qualitative data suggest that they may exert their benefits through partially distinct mechanisms.